From Waters to Screens: Wild Betta Betta spp. (Anabantiformes: Osphronemidae) Trading in Indonesia’s Online Marketplaces - Nur Arifah; Diah Komala Sari; Gusti Ayu Widayanti; Randi Syafutra; Ina Aprillia; Muhammad Iqbal (BIO PALEMBANICA, 2025)
Indonesia hosts a remarkable diversity of freshwater fishes, including numerous endemic wild Betta Betta spp. (Anabantiformes: Osphronemidae). However, the rise of e-commerce has facilitated unregulated online trade of wild Betta species. This study investigates the diversity, conservation status, and trade dynamics of wild Betta species between 1–21 October 2025, in Indonesia’s three largest online marketplaces: Shopee, Tokopedia, and Lazada. A total of 38 wild Betta species were identified, including five Critically Endangered, eleven Endangered, and seven Vulnerable taxa. The trade was dominated by species from Sumatra and Kalimantan, which together accounted for over 85% of endemic taxa. Market analysis revealed a positive correlation between rarity and price, with Endangered and Not Assessed species commanding the highest average prices. The presence of Critically Endangered species such as Betta hendra and B. burdigula indicates ongoing extraction from the wild despite conservation risks. Furthermore, nearly 26% of traded species remain Data Deficient or Not Assessed, reflecting critical knowledge gaps that hinder management and policy enforcement. The findings underscore the urgent need for stronger regulation of digital wildlife trade, improved conservation assessments, and promotion of captive breeding programs to reduce wild collection pressure.